Direct and indirect cost of managing alzheimer's disease and related dementias in the United States. (4th March 2017) - Deb, Arijita; Thornton, James Douglas; Sambamoorthi, Usha; Innes, Kim
ABSTRACT: Introduction : Care of individuals with Alzheimer's Disease and Related Dementias (ADRD) poses special challenges. As the disease progresses, individuals with ADRD require increasing levels of medical care, caregiver support, and long-term care which can lead to substantial economic burden. Areas covered : In this expert review, we synthesized findings from studies of costs of ADRD in the United States that were published between January 2006 and February 2017, highlighted major sources of variation in costs, identified knowledge gaps and briefly outlined directions for future research and implications for policy and program planning. Expert commentary : A consistent finding of all studies comparing individuals with and without ADRD is that the average medical, non-medical, and indirect costs of individuals with ADRD are higher than those without ADRD, despite the differences in the methods of identifying ADRD, duration of the study, payer type and settings of study population. The economic burden of ADRD may be underestimated because many components such as direct non-medical costs for home safety modifications and adult day care services and indirect costs due to the adverse impact of ADRD on caregivers' health and productivity are not included in cost estimates.